Increasing Preparedness Against Earthquake and Tsunami Hazards by Educating and Training a Community in Sipora Island, Indonesia - Rusnardi Rahmat Putra; Yasuke Ono; . Edidas; Iskandar G Rani; Rizky Indra Utama (Aceh International Journal of Science and Technology, 2021)
This research introduces ways of preparing the community to play a direct role in reducing the risk of earthquake and tsunami disasters. Nagari Matobe is a village located in South Sipora. This location is in an earthquake tsunami-prone area. The regional government has prepared Matobe village to be a disaster-resilient village. A previous survey from 2019-2020 showed that the community of Matobe village lacked knowledge of earthquakes, tsunamis, and disaster mitigation systems. This research aimed to improve preparation for earthquake and tsunami disasters by making the people of Matobe village resilient to disasters. The steps taken to improve community preparedness were: 1. An initial survey on community conditions, buildings, soil characteristics, and the community’s preparedness to face earthquakes and tsunamis; 2. The creation of a topographic map; 3. Education and training for elementary school students, with simulations, on the mechanism of earthquakes and tsunamis, on how to evacuate and prepare for evacuation, through stories using Doraemon, Nobita, and Dorami, comic characters from Japan; 4. Providing education and training on building materials under the 2002 Indonesian building planning standards and plans for earthquake-safe buildings following the 2016 earthquake-safe building structure standards; 5. Education and training to strengthen existing buildings; and 6. A proposal for a tsunami evacuation map and the location of evacuation signs. The community in Nagari Matobe was very cooperative and took an active role during the implementation of this research. The evaluation questionnaire distributed to elementary school students showed that the students were delighted and, on average, thought that the education and training in preparedness were beneficial. This education and training became an important reference for the community and government in developing Matobe village to become a disaster-resilient village.